International open innovation strategies of firms in European peripheral regions - Jo\~ao M. Lopes; Sofia Gomes; José Castro Oliveira; Márcio José Sol Pereira Oliveira (Journal of Open Innovation: Technology, Market, and Complexity, 2022)
The involvement of companies in different open innovation activities, through knowledge outputs and inputs, has become increasingly important for the success of companies. However, the existing literature on open innovation is scarce concerning the internationalization process of companies. The internationalization of companies is fundamental in the continuous search to increase the performance of companies externally. The objective of the present research is to explain the strategic processes in the internationalization of companies located in peripheral regions at the time of the COVID-19 pandemic from the perspective of dynamic capabilities. The sample used for this research is composed of seven Portuguese companies. The methodology of qualitative nature is exploratory and uses a case study approach. Regarding the foremost modes of operation in international markets and strategies, we find that (1) companies have partnerships with local distributors or appoint exclusive importers/distributors, and (2) companies prefer to place their products in the market through their brand, "co-branded" projects with retailers, or "private label" projects. Of the seven companies under study, six use a standardization strategy, and one opts for a configuration-coordination strategy. Our findings clarified the literature on export and internationalization strategies in a peripheral country, allowing a closer incept of the organizational and dynamic capabilities and an overview of the supporting tools these companies have to compete in the global market. Our study is original because few articles study the internationalization strategies of companies at the time of the COVID-19 pandemic and in peripheral regions of Europe.
Keywords: 650; dynamic capabilities; export; internationalization; open innovation; open innovation strategy; peripheral regions; strategies